Perbaikan Sifat Reologi Visco-Elastic Aspal dengan Penambahan Asbuton Murni Menggunakan Parameter Complex Shear Modulus - Eva Wahyu Indriyati; Bambang Sugeng Subagio; Harmein Rahman (Jenderal Soedirman University, 2013)
The increasing demand of crude oil will increase the price of petroleum asphalt. Indonesia has imported asphalt to meet the need for the annually road construction and maintenance. One solution to improving the rheological properties of bitumen is by adding the harder bitumen or other chemical compound to reduce dependence to petroleum asphalt. In Indonesia there is a source of natural asphalt in Buton Island, Sulawesi with huge amount of deposit that potentially could improve the rheological properties of Pen 60/70 Petroleum Asphalt. In order to obtain a better understanding on the contribution of Asbuton to the improvement of performance on rheological properties, this research used 19 variations of Asbuton and pen 60/70 petroleum bitumen. This variation is then subjected to the basic rheology test and the mechanistic test using Dynamic Shear Rheometer. The conclusion of basic rheological performance is obtained that mixture (Asbuton and 60/70 petroleum bitumen) will increase hardness of bitumen. Conclusion on mechanistic rheological performance is that mixture (Asbuton and 60/70 petrol bitumen) will increase Performance Grade (PG) and Complex Shear Modulus (G*). The results from the analysis of Master Curve and Black Diagram, it is shown that the increasing proportion of bitumen Asbuton will decrease the phase angle (δ) but its temperature susceptibility is worse.